2019
DOI: 10.1002/cssc.201901680
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Understanding of the Redox Properties of Fluoranil Derivatives for Cathodes in Sodium‐Ion Batteries

Abstract: Despite the potential of organic cathodes in sodium‐ion batteries, their redox properties still need to be explored. In this study, a density functional theory modeling approach is employed to comprehensively investigate the redox properties and theoretical performance parameters for a selected set of fluoranil derivatives as cathode materials. The redox properties are further correlated with various characteristics including structural variations, electronic properties, and solvation. Three primary conclusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 54 publications
2
15
0
Order By: Relevance
“…The three isomers with two cyano functional groups at different positions, namely, 2CN-BQ- n where n = 1, 2, and 3, have the redox potentials ranged within 3.61–3.74 V versus Na/Na + , indicating the negligible effect of the configuration of the functional groups on the redox potential. Similar observations have been reported in previous studies. , Note that a slightly higher redox potential by 0.13 V is predicted for 2CN-BQ-1, the one with two cyano functional groups at the nearest neighboring position, as compared with the others (Figure b). In a previous study, Kim et al also reported a similar observation: the carbonyl functional groups locally concentrated at the edge of the graphene flake would be more beneficial to the improvement of the redox potential than uniformly distributed carbonyl functional groups …”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…The three isomers with two cyano functional groups at different positions, namely, 2CN-BQ- n where n = 1, 2, and 3, have the redox potentials ranged within 3.61–3.74 V versus Na/Na + , indicating the negligible effect of the configuration of the functional groups on the redox potential. Similar observations have been reported in previous studies. , Note that a slightly higher redox potential by 0.13 V is predicted for 2CN-BQ-1, the one with two cyano functional groups at the nearest neighboring position, as compared with the others (Figure b). In a previous study, Kim et al also reported a similar observation: the carbonyl functional groups locally concentrated at the edge of the graphene flake would be more beneficial to the improvement of the redox potential than uniformly distributed carbonyl functional groups …”
Section: Resultssupporting
confidence: 91%
“…∑ is the sum of the Boltzmann factors for all the three isomers. 39,48 ■ RESULTS AND DISCUSSION Seven chloranil derivatives with varied numbers of cyano functional groups, namely, tetrachloro-1,4-benzoquinone (BQ), 2-cyano-3,5,6-trichloro-1,4-benzoquinone (1CN-BQ), 2,3-dicyano-5,6-dichloro-1,4-benzoquinone (2CN-BQ-1), 2,6dicyano-3,5-dichloro-1,4-benzoquinone (2CN-BQ-2), 2,5-dicyano-3,6-dichloro-1,4-benzoquinone (2CN-BQ-3), 2,3,5-tricyano-6-chloro-1,4-benzoquinone (3CN-BQ), and tetracyano-1,4-benzoquinone (4CN-BQ), were systematically designed, as shown in Figure 1. Note that quinone derivatives with redoxactive carbonyls have been highlighted to be attractive cathode materials for lithium-ion batteries.…”
Section: ■ Computational Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous studies have highlighted that structure-derived variations in the redox properties would originate from two primary factors: (1) electronic characteristics and (2) solvation. [27][28][29][30]46 Figure 5 shows the correlations between the redox potentials and four main electronic characteristics (electron affinity, the lowest unoccupied molecular orbital (LUMO), the highest occupied molecular orbital (HOMO), and HOMO−LUMO gap).…”
Section: ■ Results and Discussionmentioning
confidence: 99%